2017
DOI: 10.1124/dmd.117.076109
|View full text |Cite
|
Sign up to set email alerts
|

Histone Modifications Regulate the Developmental Expression of Human Hepatic UDP-Glucuronosyltransferase 1A1

Abstract: Human UDP-glucuronosyltransferase 1A1 (UGT1A1) is a unique enzyme involved in bilirubin conjugation. We previously characterized the hepatic expression of transcription factors affecting UGT1A1 expression during development. Accordingly, in this study, we characterized the ontogenetic expression of hepatic UGT1A1 from the perspective of epigenetic regulation. We observed significant histone-3-lysine-4 dimethylation (H3K4me2) enrichment in the adult liver and histone-3-lysine-27 trimethylation (H3K27me3) enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Moreover, a strong Asian linkage is not surprising, as PI are theorized to have originated in Asia and mixed extensively with Melanesians both depositing and accumulating genes into their genomes during colonization of the Pacific Islands [ 33 ], which has been further corroborated by both Y chromosome and mitochondrial DNA analyses [ 34 ]. Finally, our work is complemented by recent data demonstrating that hepatic UGT1A1 can be regulated during early human development by histone modification [ 35 ], a novel and interesting finding that supports the concept that UGTs can be regulated at the transcriptional level through genetic mechanisms. Having said this, we believe that future work in this area will need to encompass protein-level studies with Western blot of UGT2B15 and/or activity studies to confirm if these results found at the mRNA levels also follow through to the levels of enzyme proteins and their function.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, a strong Asian linkage is not surprising, as PI are theorized to have originated in Asia and mixed extensively with Melanesians both depositing and accumulating genes into their genomes during colonization of the Pacific Islands [ 33 ], which has been further corroborated by both Y chromosome and mitochondrial DNA analyses [ 34 ]. Finally, our work is complemented by recent data demonstrating that hepatic UGT1A1 can be regulated during early human development by histone modification [ 35 ], a novel and interesting finding that supports the concept that UGTs can be regulated at the transcriptional level through genetic mechanisms. Having said this, we believe that future work in this area will need to encompass protein-level studies with Western blot of UGT2B15 and/or activity studies to confirm if these results found at the mRNA levels also follow through to the levels of enzyme proteins and their function.…”
Section: Discussionsupporting
confidence: 70%
“…They found that high expression of UGT1A1 in the adult liver was related to enrichment of the transcriptional activation marker H3K4me2. The inhibition of fetal UGT1A1 expression was consistent with the high enrichment of enhancer of zest homolog 2 (EZH2) of the UGT1A1 promoter and the transcriptional suppression marker H3K4me3 (catalyzed by EZH2) [ 58 ]. Children with hyperbilirubinemia are more likely to develop infection during clinical treatment.…”
Section: Epigenetics In Ugt1asmentioning
confidence: 72%
“…Histone modifications are regulated while regulating gene expression. Knockout of the TF HNF1α has been confirmed to reduce the enrichment of H3K4me2 in the promoter region of UGT1A1 [ 58 ]. Oxidative stress can regulate histone-related enzymes to upregulate the level of H3K4me2 [ 68 ].…”
Section: Epigenetics In Ugt1asmentioning
confidence: 99%
“…Chromatin Immunoprecipitation (ChIP) analysis was performed using frozen liver samples, as described previously [ 20 , 28 , 29 ], with minor modifications. Briefly, approximately 100 mg liver samples were crosslinked with 1% formaldehyde for 10 min and halted by 125 mM glycine.…”
Section: Methodsmentioning
confidence: 99%